IMPROVING VOCABUALARY ACHIEVEMENT THROUGH TOTAL PHYSICAL RESPONSE AMONG GRADE FOUR ELEMENTARY SCHOOL PUPILS - Caroline V. Katemba; Kisan Tampubolon (Journal of Language Pedagogy, 2011)
This research is on Improving Vocabulary Achievement Through Total PhysicalResponse (TPR) among Grade Four Karyawangi Elementary School Pupils. It is administeredto answer question”Is TPR method effective in improving the vocabulary achievement of thepupils?” The data were collected through pre test and post test, administered to 31 students andwas analyzed by using t-test. The achievements showed that the mean of the pre-test was 23.06and the mean of the post-test was 64.11, while the significant = 0.003 < Î± = 0.05, thus theconclusion that there is a significant difference in pupils’ vocabulary achievement throughTotal Physical Response (TPR).